Representasi Nilai-Nilai Kehidupan Dalam Film Petualangan Sherina (Tahun 2000) Karya Sutradara Riri Riza: Kajian Sosiologi Sastra - Anindya Putri Salsabila; Yuniseffendri (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This research aims to describe the types of life values represented in the film Petualangan Sherina (2000) by Riri Riza, examine their relation to the social life realities of Indonesian society, and analyze the potential functions of these values for the community. This research uses a qualitative descriptive method with a literary sociology study based on Ian Watt's perspective, combined with Stuart Hall's constructionist representation concept and Haris Supratno's nine-value concept. Data in the form of dialogs and song lyrics were collected thru the observation-note technique and analyzed thru the stages of identification, classification, interpretation, and conclusion drawing. The research findings revealed 51 data points from nine types of life values, which consist of educational values, religious values, heroism values, leadership values, simplicity values, courage values, sacrifice values, mutual cooperation values, and moral values. The representation of these values is related to the social life realities of Indonesian society, both in the post-reform context when the film was produced and in the current social conditions of the present generation. This film has the potential to serve as both an entertainment medium and a social influence. Four potential functions for society as a social influence have been identified, namely didactic function, moral function, social function, and humanistic function.